(untitled) (Web of Teachers: Inderscience Research, 2025)
This article explores the significance of organizing extracurricular activities in primary grades and the teacher’s role in this process. Extracurricular activities are vital for identifying students’ interests, fostering their creative potential, and developing social skills. Drawing on personal experience and practical examples, the article analyzes how teachers can unlock students’ talents and motivate them for further growth. Successful implementation of extracurricular activities enhances students’ interest in learning and ensures their comprehensive development.